The control of rat-heart phosphofructokinase by citrate and other regulators - Pogson, C. I. (1966)
1. The effects of ATP, inorganic phosphate and citrate on the relationship between fructose 6-phosphate concentration and initial velocity of reaction has been investigated with a partially purified preparation of rat-heart phosphofructokinase. 2. At low concentrations of ATP (<80μm) rate curves for fructose 6-phosphate approximated to Michaelis–Menten kinetics. At higher ATP concentrations rate curves were sigmoid, the K(m) for fructose 6-phosphate increased and the reaction appeared to be first-order with respect to fructose 6-phosphate at concentrations above its K(m) and of a higher order at concentrations below its K(m). Inorganic phosphate lowered the K(m) for fructose 6-phosphate and the concentration at which the apparent kinetic order decreased. 3. At 40μm-ATP, citrate was an activator at low concentration (<100μm) and an inhibitor at higher concentrations. At 0·5mm-ATP, citrate was inhibitory at all concentrations tested. 4. A new method for phosphofructokinase assay using [U-(14)C]fructose 6-phosphate is described which allows measurements to be made of the velocity of the forward reaction at known concentrations of the products of the reaction. With this method confirmatory evidence has been obtained that concentrations of ATP, AMP, phosphate and citrate may regulate phosphofructokinase in the perfused rat heart.